Gastric mucosal blood flow and acid secretory changes in man with impromidine: a new specific histamine-H2-receptor agonist. Issue 7 (July 1981) - McIsaac, R L; Johnston, B J; Fielding, L P
Abstract : The effect of impromidine, a new histamine-H2-receptor agonist, on gastric mucosal blood flow (neutral red clearance) and acid secretion was studied in nine volunteers. Impromidine stimulated a dose-dependent increase in neutral red clearance and acid secretion. Simultaneous cimetidine in three doses caused a parallel shift to the right for both acid output and clearance with unchanged maxima compatible with simple surmountable antagonism. There were small cardiovascular changes: an increased heart rate with a decreased diastolic pressure during infusion of impromidine. These changes were antagonised by cimetidine.